GOOGLE TRANSLATE AS ENGLISH LEARNING TOOL ASSISTANCE FOR NON-ENGLISH DEPARTMENTS STUDENTS: STUDENTS’ PERCEPTION - Salasiah Ammade; Muh Fitra Ramadhani; Ali Wira Rahman (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This Google translation (GT) is one of main importance tool for students in assisting them in translating English words or sentences. Many researches have investigated its importance to aid students in learning, but still limit research focuses on how GT as English learning tool assist non-English department student. The current research tries to fill the gap by researching how Google translates support non-English department students in learning English viewed from students’ lens. This research used qualitative research, using case study. The participants of this research consist of 10 non-English students in Faculty of Teacher Training and Education of Universitas Muhammadiyah Parepare. The researcher conducted interview via WhatsApp voice note to obtain the data from the participants. The data then analyzed using Miles & Huberman pattern. The result of this research showed that GR is a good application to support non-English students in learning English. It was found that the app become very helpful tool in learning English with variety features like, direct typing translates, camera translate, offline translate, voice translate, and easy to use tool to enrich English vocabulary, enrich English sentences, pronouncing appropriate English words. Beside many advantages, the result also showed that GT still has trouble in it like wrong translation in what the learner wanted to know the translation. Another result showed that to get better translation we need to use online GT especially in translate long sentence. It can be concluded that Google translating tool can be chosen as main supplementary learning tool particularly in learning English.